SWOT Analysis at The Lambung Mangkurat Medical Center Clinic in Banjarbaru - Alin, Dhemes; Sanyoto, Didik Dwi; Iskandar, Iskandar (Lambung Mangkurat, 2024)
Lambung Mangkurat Medical Center (LMMC) Banjarbaru Clinic has only focused on providing health services without any evaluation of achievements. The facilities and infrastructure are inadequate to support health services. Additionally, financial governance and Human Resources (HR) management are not yet optimal. The purpose of this study is to analyze SWOT at the Lambung Mangkurat Medical Center (LMMC) Clinic as a guide for running a better and more focused. This type of research using quantitative methods with descriptive observational design. The object of this research is the LMMC Banjarbaru Clinic. This research was carried out in March 2024 at the LMMC Clinic in Banjarbaru. Quantitative analysis was obtained by SWOT (Strength, Weakness, Opportunity, Threat) analysis. Based on the results of this study there was the LMMC clinic in quadrant 1, which means this position supports an aggressive strategy where the clinic has opportunities and strengths.